Complete genome sequence and taxonomic clarification of the DN2 strain of duck hepatitis a virus genotype III (DHAV-3) first time isolated in Vietnam - Huong, Doan Thi Thanh; Hiên, Nguyễn Bá; Hạnh, Trần Xuân; Hòa, Lê Thanh (Vietnam Journal of Biotechnology, 2012)
The entire nucleotide sequence of 7777 bp for the complete genome of a virulent strain of duck hepatitis A virus (DHAV) first time isolated in Vietnam, designated as DN2, was obtained and taxonomically identified to genotype III (DHAV-3). The complete genomic sequence was obtained by segmented PCR amplification, using 5 overlapping anchor-primer pairs, with cDNA template converted from the RNA genome by random hexamer and by direct sequencing. The deduced gene order consists of 3 major parts, subsequently, a non-coding region of 652 bp at 5’ (5’UTR) as first region, followed up by an open reading frame (ORF) encoding for a polyprotein; and last, a non-coding region of 369 bp at 3’ (3’UTR), ending with a poly-A sequence. ORF of the genome comprises of 6756 bp coding 2251 amino acids, including 12 compositional polypeptides such as L; VP0, VP3, VP1 (P1 comple); 2A1, 2A2, 2B, 2C (P2 complex); and 3A, 3B, 3C, 3D (P3 complex). Cleavage of 12 compositional proteins occured at sites of amino acids L/G, Q/G, Q/S, E/L, NPG/P as determined according to Ding, Zhang (2007). Compared with genome of the AP-04114 strain (Korea, GenBank: DQ812093) of DHAV-3 genotype, it revealed that gene order and size of each compositional genes in the open reading frame in the DN2 genome are the similar, except 2 nucleotides missing in the 3’UTR. Compared to a strain of DHAV-1 (C80, GenBank: DQ864514) and DHAV-2 (strain 04G, GenBank: EF067923), it revealed that the size of all DNA region coding for 11 proteins is similar, with an exception of VP1 that size of this gene is of 720 bp in the strains DHAV-3 and 714 bp in the strains of DHAV-1. Non-coding region in the strains of DHAV-1 (ie. strain C80) is the shortest (626 bp at 5’UTR and 315 bp at 3’UTR).